Apropriação do pensamento computacional e da robótica educacional para um currículo alinhado às novas tendências em tecnologias educacionais - Peters, Marcio (2023)
Based on the BNCC (Base Nacional Comum Curricular), the objective of this work is to promote educational robotics and computational thinking in mathematics teaching. Considering the absence of the theme in the ES Curriculum, to encourage the practice of the theme, based on specialists, we propose relevant activities that will help teachers in their work, inside and outside the classroom. To this end, we created a series of six learning circuits composed of didactic workshops. In sequence, the circuits were designed in such a way that they approach that provide the development of computational thinking skills and educational robotics in the teaching of mathematics with the use of the tools “X Logo”, Code.org, Tinkercad, Arduino, “App Inventor” and unplugged computing activities, in case of not having access to a computer or similar. This culminated in training for education professionals in partnership with the Secretary of Education of the State of Espírito Santo.